Modelling the impact of corporate sustainability on economic performance with reference to Indian financial industry. (3rd April 2020) - Sharma, Geeti; Gupta, Sahil
Corporate sustainability is a buzzword these days and is instrumental in achieving a comparative advantage by the corporates. The study intends to study the influence of corporate sustainability on economic performance concerning the Indian banking industry. Structural equation modelling, a multivariate technique, is employed in this study to measure the relationship between corporate sustainability and economic performance. Results show the significant but moderate positive relationship between economic performance and corporate sustainability. The findings would be beneficial to the experts in the allocation of limited resources to improve the corporate sustainability performance of firms, particularly in the Indian banking sector.